The Art Reference Library of the North Carolina Museum of Art - Thomas, William Joseph (My University, 2014)
Many people have visited the North Carolina Museum of Art in Raleigh. Perhaps fewer have visited the Art Reference Library of the North Carolina Museum of Art—but more should! The Museum Library provides a non-circulating collection of more than 40,000 volumes and selected electronic resources to serve the research needs related to the Museum. Museum Librarian Natalia Lonchyna described the Library, its resources and services recently.
Keywords: Art libraries; North Carolina Museum of Art